EVALUATION OF AN IMMUNOHISTOCHEMICAL TECHNIQUE FOR THE DIAGNOSIS OF MIXED MAMMARY TUMORS IN BITCHES - Rodríguez C., Cyntia (2013)
The aim of the study was to evaluate an immunohistochemical technique for the diagnosis of canine mixed mammary tumors (CMMT) using anti-cytokeratin AE1/AE3 and anti-vimentin monoclonal antibodies that are routinely used in the diagnosis of human mammary tumors. Twenty paraffin tissue blocks of canine mixed mammary tumors, previously diagnosed by hematoxilin-eosin (HE) histopathology were used. Three slides sets, 4 μm thick, were obtained per viability of the tissue, and the other two were used for the immunohistochemistry through the Streptavidin-Biotin-labeled method. Epithelial cells positively reacted against the anti-cytokeratin AE1/AE3 showing a brown colour at the cytoplasma level. Fibroblasts, connective tissue, myoepithelial cells, cartilage cells and bone areas showed a brown colour against the anti-vimentin antibody. All benign tumors reacted positively to both antibodies, whereas 73% malign tumors were positive with the anti-cytokeratin antibody. It is concluded that mixed mammary neoplasm in dogs may be diagnosed by the technique of immunohistochemistry using monoclonal antibodies used in the detection of human mammary tumors. block. One was stained with HE to confirm the